2012
DOI: 10.1177/1352458512468498
|View full text |Cite
|
Sign up to set email alerts
|

Early switch to fingolimod may decrease the risk of disease recurrence after natalizumab interruption

Abstract: Figure 1. Relapses (black bars) occurring during observation in untreated subjects (U1-U4), subjects who shifted to other immunomodulatory drugs (IM1-IM4) or to fingolimod (F1-F11).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 7 publications
1
24
0
Order By: Relevance
“…The only available data derive from case reports and observational studies on MS patients who switched from natalizumab to fingolimod, generally showing a disease reactivation after the switch with few exceptions [16,17,18,19,20,21]. It has been suggested that early fingolimod start (i.e., before the end of the recommended natalizumab 3-month washout interval) might prevent relapse occurrence [22,23].…”
Section: Discussionmentioning
confidence: 99%
“…The only available data derive from case reports and observational studies on MS patients who switched from natalizumab to fingolimod, generally showing a disease reactivation after the switch with few exceptions [16,17,18,19,20,21]. It has been suggested that early fingolimod start (i.e., before the end of the recommended natalizumab 3-month washout interval) might prevent relapse occurrence [22,23].…”
Section: Discussionmentioning
confidence: 99%
“…De Seze et al observed a reduction in the proportion of clinical relapses in patients who had started FTY within three months of discontinuing NAT compared to patients who had started FTY more than three months after NAT suspension [25]. The benefits of FTY after NAT compared to interferon beta-1a or glatiramer acetate or no treatment is also described in a small series by Laroni et al [26]. The French multicentre observational study ENIGM (Enquete Nationale concernant l'Introduction du fingolimod en relais au natalizumab) observed a clinical relapse in 27% of patients during the washout period from NAT to FTY, perhaps reflecting a poor control of disease activity during NAT treatment; in fact, only 39% of patients stopped NAT exclusively for safety reasons [27].…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have also reported a considerable risk of reactivation following fingolimod use after NTZ [17,18,19,20,21]. Exceptions to these findings have been observed for shorter time intervals to switching NTZ, pointing out the importance of early initiation of alternate treatment in reducing the risk of recurrence of disease [11,22,23,24]. Recent evidence with newer oral therapies is clear in showing that switching from NTZ to dimethyl fumarate results in increased relapses [25].…”
Section: Introductionmentioning
confidence: 99%